Initial clinical experience with magnetic resonance-guided radiotherapy in pediatric patients: Lessons learned from a single institution with proton therapy - Hall, Matthew D.; Mittauer, Kathryn E.; Herrera, Roberto; Von Werne, Katherine; Kotecha, Rupesh; Kalman, Noah S.; McCulloch, James; Alvarez, Diane; McAllister, Nicole C.; Doty, Delia G.; Rzepczynski, Amy E.; Deere, Will; et al. (Frontiers in Oncology, 2023)
Purpose/Objectives: Magnetic resonance-guided radiotherapy (MRgRT) is increasingly used in a variety of adult cancers. To date, published experience regarding the use of MRgRT in pediatric patients is limited to two case reports. We report on the use of MRgRT for pediatric patients at our institution during a four-year period and describe important considerations in the selection and application of this technology in children. Materials/Methods: All patients treated with MRgRT since inception at our institution between 4/2018 and 4/2022 were retrospectively reviewed. We also evaluated all pediatric patients treated at our institution during the same period who received either imaging or treatment using our magnetic resonance-guided linear accelerator (MR Linac). We summarize the clinical cases where MRgRT was selected for treatment in our clinic, including disease outcomes and toxicities. Results: Between 4/2018 and 4/2022, 535 patients received MRgRT in at our center, including 405 (75.7%) with stereotactic ablative radiotherapy (SABR). During this period, 347 distinct radiotherapy courses were delivered to pediatric patients, including 217 (62.5%) with proton therapy. Four pediatric patients received MRgRT. One received SABR for lung metastasis with daily adaptive replanning and a second was treated for liver metastasis using a non-adaptive workflow. Two patients received fractionated MRgRT for an ALK-rearranged non-small cell lung cancer and neuroblastoma. No Grade 2 or higher toxicities were observed or reported during MRgRT or subsequent follow-up. Twelve patients underwent MR imaging without contrast during treatment for brain tumors to assess for tumor/cystic changes. Two patients treated with other modalities underwent MR simulation for target volume delineation and organ at risk sparing due to anatomic changes during treatment or unexpected delays in obtaining diagnostic MR appointments. Conclusions: In four pediatric patients treated with MRgRT, treatment was well tolerated with no severe acute effects. At our center, most pediatric patients are treated with proton therapy, but the cases selected for MRgRT demonstrated significant organ at risk sparing compared to alternative modalities. In particular, MRgRT may provide advantages for thoracic/abdominal/pelvic targets using gated delivery and adaptive replanning, but selected patients treated with fractionated radiotherapy may also benefit MRgRT through superior organ at risk sparing.